Variety of functions and effects of kisspeptin - Matvienko, M.G.; Pustovalov, A.S.; Dzerzhinsky, N.E. (Вiopolymers and Cell, 2013)
A brief review of the literature on the properties and efficacy of kisspeptin, in particular, for the regulation of en- docrine functions. The results of numerous experiments with kisspeptin in molecular biology, reproductive medicine and endocrinology, as well as the development of vaccines against malignant tumors, are analyzed. Kisspeptin is known to initiate a cascade of changes leading to the puberty. According to the reports, this peptide modifies the activity of glands that produce sex hormones, so it can be used in the treatment of diseases associated with the violation of puberty, especially amenorrhea in adolescent girls. The effect of this peptide is related to the activation of hypothalamic cells that produce GnRH, which regulates a level of gonadotropin-releasing hormone. Thus, kisspeptin can activate the reproductive system without violating the protective mechanisms of orga- nism. The in-depth research of kisspeptin effects on all parts of the hypothalamic-pituitary-gonadal axis is promising, as well as the investigation of neuron-glial interactions in the central nervous system under the influence of this peptide. Представлено короткий огляд літературних даних з дослідження властивостей та ефективності застосування кіспептину, зокрема, для регуляції ендокринних функцій організму. Проаналізовано численні результати експериментів з використанням кіспептину в молекулярній біології, репродуктивної медицині, ендокринології, а також при розробці вакцин проти злоякісних утворень. Згаданий пептид ініціює каскад змін, які призводять до пубертату. За наявними даними, кіспептин змінює активність залоз, які продукують статеві гормони, внаслідок чого він може знайти застосування у лікуванні захворювань, пов’язаних з порушенням пубертату, зокрема, аменореї у дівчат-підлітків. Дія цього пептиду обумовлена активацією клітин гіпоталамуса, що виділяють гонадоліберин, який регулює рівень гонадотропних гормонів. У той же час кіспептин активує репродуктивну систему, не порушуючи при цьому захисних механізмів організму. Видається перспективним більш поглиблене вивчення ефекту кіспептину на всі ланки гіпоталамо-гіпофізарно-гонадальної осі, а також дослідження нейроно-гліальних взаємодій у центральній нервовій системі під впливом даного пептиду. Представлен краткий обзор литературных данных по исследованию свойств и эффективности применения кисспептина, в частности, для регуляции эндокринных функций организма. Проанализированы многочисленные результаты экспериментов с использованием кисспептина в молекулярной биологии, репродуктивной медицине, эндокринологии, а также при разработке вакцин против злокачественных образований. Указанный пептид инициирует каскад изменений, ведущих к пубертату. По имеющимся данным, кисспептин изменяет активность желез, продуцирующих половые гормоны, вследствие чего он может найти применение в лечении заболеваний, связанных с нарушением пубертата, в частности, аменореи у девочек-подростков. Действие данного пептида связано с активацией клеток гипоталамуса, выделяющих гонадолиберин, регулирующий уровень гонадотропных гормонов. В то же время кисспептин активирует репродуктивную систему, не нарушая при этом защитных механизмов организма. Представляется перспективным более углубленное изучение эффекта кисспептина на все звенья гипоталамо-гипофизарно-гонадальной оси, а также исследование нейроно-глиальных взаимодействий в центральной нервной системе под влиянием данного пептида.